Exhuming the Top End of North America: Episodic Evolution of the Eurekan Belt and Its Potential Relationships to North Atlantic Plate Tectonics and Arctic Climate Change. Issue 12 (11th December 2019) - Vamvaka, Agni; Pross, Jörg; Monien, Patrick; Piepjohn, Karsten; Estrada, Solveig; Lisker, Frank; Spiegel, Cornelia
Abstract: We present the first low‐temperature thermochronology data from northernmost Ellesmere Island (Canadian Arctic), along with palynological data from Paleogene sediments. Our study area is part of the >2, 500‐km‐long Eurekan deformation belt that formed across the High Arctic during the Eocene. The aim of this study is to investigate the exhumation of the Eurekan belt and potential relationships with the opening of the North Atlantic, as well as with environmental changes of the Arctic. Our data show that the Canadian Arctic margin was characterized by stretching and basin formation during the Paleocene. Sediment deposition occurred in a coastal swamp environment under a warm and humid climate that lasted into the early Eocene. Exhumation of northern Ellesmere Island was episodic and was presumably controlled by strike‐slip movements along the De Geer Fracture Zone between Svalbard and Greenland. Enhanced exhumation of northern Ellesmere Island occurred 66–60 Ma, 55–48 Ma, 44–38 Ma, and 34–26 Ma. These exhumation periods largely correlate with changes of spreading rates and movement directions of the Norwegian‐Greenland Sea. Main topographic growth along the Eurekan belt was temporally coincident with deposition of ice‐rafted debris off eastern Greenland. We suggest that Eurekan topography growth was an important trigger for glacier formation in Greenland. The cessation of rapid exhumation at 26 Ma can be explained by continental separation between Greenland and Svalbard, which decoupled northern Ellesmere Island from strike‐slip movements along the De Geer Fracture Zone, eventually leading to the opening of the Fram Strait. Key Points: Thermochronology data suggest Eocene high‐latitude rapid exhumation and topography formation Intracontinental Eureka Orogeny seems to be controlled by far‐field effects of North Atlantic spreading Rise of the Eureka Belt starts at warm and humid conditions and may have triggered subsequent Arctic glaciation